Webster's II new Riverside University dictionary - Soukhanov, Anne H (Houghton Mifflin, 1984)
Defines 200,000 words including 25,000 new words. Features word histories, usage notes, synonym paragraphs, and style, diction, and writing guides.
Keywords: lingvistika, lékařská terminologie; lingvistika; angličtina; Linguistics